The possibilities of RFID and NFC tag implementation in dairy segment - Žurbi, Tina (Journal of Print and Media Technology Research, 2023)
With the help of printed electronics, the product-consumer relationship can be further evolved and explored, thus enabling the building of a deeper emotional connection. The growing implementation of online connectivity – Internet of things, is one of the important driving factors for the printed electronics market. The goal of our study was to estimate implementation options of printed electronics into the packaging of dairy products according to the type of packaging with considering the approximation of the cost per unit. Knowing that the dairy segment is mainly a commodity, we assume this implementation will have a big influence on the product price. Our research showed that the added value in the commodity segment is too low to be able to cover the cost of implementation of the RFID tag. Printed electronics and, generally speaking, smart packaging has found its place in a segment where a need for security elements or the product is higher priced and the extra cost of a tag does not represent a high burden. There is a great potential in the packaging of pharmaceutical and cosmetic products, where the product’s identity is key. There is also a potential in a food segment where food safety is crucial; these are nutritional products for children, for example, baby milk. The main obstacles of printed electronics and smart labels, in general, are in the high unit price per product because the uses are mostly carried out on luxury goods and those are smaller in quantities. Taking it into consideration the printed electronics providers cannot achieve large quantity productions and therefore lowering of price because the economy of scale is insufficient. Until there are no implantations in the segments where the quantities are high, the RFID tag has lesser chance to get its price lowered.